2016
DOI: 10.4314/ejesm.v9i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Governing agricultural drought: Monitoring using the vegetation condition index

Abstract: This paper investigates the spatial and temporal aspect of seasonal agricultural drought in Ethiopia during the cropping season using Vegetation Condition Index. SPOT-VGT S10 NDVI time-series for the period 1998 to 2013 was employed. Five hundred and sixty-seven dekadal images were administered in order to produce the multi-temporal agricultural drought maps. Accordingly, the analysis showed different causes for the nation-wide drought events occurred in the years . The study provides key information on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
(41 reference statements)
1
7
0
1
Order By: Relevance
“…On the other hand, the years 2001,2005,2006,2007,2013,2016, and 2018 reflected near-normal NDVI throughout most of the rain-fed agriculture regions. These results are coherent with the findings of previous studies in indicating the onset, spatial, and temporal dynamics of agricultural drought in Ethiopia [18]. Pixel-based trend analysis showed that a significant precipitation decrease in the central areas is accompanied by a significant increase in LST.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the years 2001,2005,2006,2007,2013,2016, and 2018 reflected near-normal NDVI throughout most of the rain-fed agriculture regions. These results are coherent with the findings of previous studies in indicating the onset, spatial, and temporal dynamics of agricultural drought in Ethiopia [18]. Pixel-based trend analysis showed that a significant precipitation decrease in the central areas is accompanied by a significant increase in LST.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, NDWI is defined in a similar way to NDVI but uses the near-infrared channel to monitor the water content of the vegetation canopy. Fluctuations in the vegetation canopy are indicators of drought stress [18]. Besides NIR and SWIR, two spectral regions of the electromagnetic spectrum have been found to be useful for the detection of plant water content: the green and red channels.…”
Section: Datasetsmentioning
confidence: 99%
“…Many drought studies have focused on assessment of both meteorological and agricultural droughts in Ethiopia. While Gebrehiwot et al (2016) undertook a determination of spatiotemporal seasonal agricultural drought in Ethiopia during the 1998 to 2013 cropping seasons; Suryabhagavan (2017) characterized meteorological droughts and climate variability in Ethiopia over three decades (1983 to 2012). The study of Qu et al (2019) on impacts of drought, includes other countries aside Ethiopia and covering the Horn of Africa, while that of Gidey et al (2018) characterized the occurrence of drought in northern Ethiopia for 15 years (2001 to 2015).…”
Section: The Commonly Used Meteorological Drought Indicators Include mentioning
confidence: 99%
“…The study of Gebrehiwot et al (2016), classi es Tigray as one the 'most severely affected (regions) during well-known famines', where a slight rainfall-de ciency can result in crop failure, with a direct impact on food security of households. Crop failure has been attributed to the paltry amount of water stored in the soil during a prolonged dry spell (Marteau et al, 2011;Mugalavai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, se ha seleccionado únicamente desde 2001, haciendo coincidir así los años de las series temporales de precipitación y NVDI. La decisión de emplear los mismos años se ha basado en estudios similares a este donde se opta por emplear series temporales de la misma longitud temporal (Boschetti et al, 2013;Gebrehiwot et al, 2016;Njery, 2016).…”
Section: Materialesunclassified